Diagnostic and Therapeutic Approach to Autoimmune Neurologic Disorders - López-Chiriboga, A. Sebastian; Flanagan, Eoin P. (Seminars in Neurology, 2018)
The field of autoimmune neurology is evolving rapidly. The discovery of autoantibodies that target neural antigens has expanded swiftly in the last decade. Recognition of the clinical syndromes associated with autoimmune neurologic disorders, and our understanding of the pathophysiology, has progressed significantly. Radiographic, electrophysiological, and laboratory testing (particularly neural autoantibody testing) are fundamental in the diagnosis of autoimmune neurological disorders and in the exclusion of mimics. Furthermore, investigations may serve as a baseline from which objective assessment of improvement or detection of relapse can be made. These disorders can be associated with underlying neoplasms, and screening for malignancy is an essential component of the investigations. Early diagnosis and prompt initiation of immunotherapy can improve neurologic function. The use of immunotherapy, however, can be associated with diverse side effects, and careful monitoring is crucial to prevent complications. Herein the authors address the diagnostic and treatment approach of autoimmune neurologic disorders, with particular focus on antibody-mediated neurologic autoimmunity.
Keywords: autoimmune encephalitis; immunotherapy; immunosuppressive medications; autoimmune neurology